Corrective effects of different training options on development and maturation of professional motor skills from dominant and non-dominant legs of young soccer players. - Witkowski, Z.; Lyakh, V.; Gutnik, B.; Lipecki, K.; Rutowicz, B.; Penchev, B.; Pencheva, L. (Journal of Physical Education and Sport, 2011)
The purpose of this study is to investigate the effects of the different options of special technical training on development of motor skills in effective performance of dominant and non-dominant legs of young footbolers. 47 volunteer male soccer players (13 years of age) from three soccer teams participated in the study. Young athletes were divided into two experimental (E1 and E2) and one control (C) groups. There were no significant difference between individuals. Investigation was carried out for 1 year - 3 days per week. The participants were tested three times. Each training session included different training modes of specific corrective exercises. In group E1 the corrective ratio of usage of subdominant/ dominant leg was 4; In group E2 the ratio was 1:1. In the control group all training sessions were conducted in traditional way in which 80-90% of time players used only leading leg as manipulative. Six professional technical skills were subjected to evaluation. Results were processed using the method of analysis of variance and post-hoc Tukeya´s test. Both versions of specific training ratio of the legs have resulted to a significant advantage in effectiveness of motor performance (p <0,05-0,001) in both experimental groups (E1 and E2) over the control (C). This advantage was apparent in a number of qualified sport techniques performed with both legs. More effective uni- and bilateral formation of the specific soccer skills was demonstrated in experimental group E1, despite a lesser number of corrective training hours during one year of training. In the end of the experiment significant differences between dominant and non dominant legs in experimental and control groups were sen. This fact may indicate that an adolescent have some potential for future maturation of the manipulative skills from non dominant leg in terms of development of more expressive bilateral behavior.